Estudo de fatores que interferem na qualidade das aplicações terrestres de produtos fitossanitários - León, Roxanna Patricia Palma (2021)
Chemical control remains an effective way of managing pests, diseases and weeds. However, it is necessary to combine parameters and factors involved in pesticides applications, prioritizing them according to their influence on the quality of the application, in order to guarantee the correct deposit of the active ingredient in the target, safely and without losses. To keep these processes under control, constant monitoring and research of both new technologies and new combinations of existing ones is necessary to preserve viable molecules and without causing contamination to the environment. Thus, the objective of this work was to study three of the factors that influence the quality of ground applications of pesticides and determine the sample size for evaluations of spray deposition in ground applications for coffee (Coffea arabica L.), corn (Zea mays L.) and soybean (Glycine max L.). For this, the research was divided into two parts. The first corresponds to the sample size to evaluate spray deposition on the leaves of the crops, in the upper and lower thirds for soybeans and coffee and for corn, the middle third was also added. The size of the basic experimental unit was first determined by studying the coefficients of variation calculated for sets containing between 1 and 20 leaves for soybean and coffee and between 1 and 8 leaves for corn. It was established at 10 leaves per set for coffee and soy and at 2 leaves per set for corn. Then, the sample size was determined using the modified maximum curvature and maximum curvature of the variation coefficient methods. It was determined for coffee between five and eight sets of leaves for spray deposition, and four to five Petri dishes for losses to the soil. In corn, a sample size was defined between five and nine sets of leaves and between four and five Petri dishes. In soybeans, between four and five sets of leaves and six Petri dishes were defined. In the second part, the factor with the greatest influence on the quality of the applications of pesticides was determined between the droplet size, application rate and the use of adjuvants using multivariate statistics. Spray deposition on the leaves of the upper, middle and lower thirds was evaluated in the 3 crops, in the coffee the canopy was also separated in the interior and exterior region; run-off to the ground with Petri dishes placed before application and also coverage area, droplet density, relative amplitude and diameter of the volumetric median on water-sensitive papers. It was found that droplet size is the most influential factor in the quality of application of phytosanitary products in the three crops. The second factor will depend on the analyzed variable, when the evaluation is focused on the spray deposition on the leaves, it will be the use of adjuvants and the interaction between application rate and use of adjuvants. When the evaluation is focused on coverage and droplet density, the second factor will be the application rate.